Níveis de gravidade da periodontite e anemia de doença crônica em gestantes - Pimenta, Rodolfo Macedo Cruz (2016)
Periodontitis is the second most frequent oral disease in the world and it is defined as an infection of periodontal supporting tissues associated with bacterial biofilm accumulation on the tooth surface. The hypothesis that periodontitis is associated with systemic repercussions has drawn the attention of the scientific community, including its contribution to the development of anemia, which in pregnancy may be related to undesirable outcomes. Most cases of anemia during pregnancy can not be originally iron deficiency, but due to chronic inflammation that characterizes anemia of chronic disease (ACD). Nonetheless, the possible association between the two diseases is related to iron metabolism. This study investigated the influence of different levels of periodontitis severity in anemia of chronic disease in pregnant women. Methods: Cross-sectional study was conducted in Santo Antonio de Jesus, Bahia, Brazil, from February 2014 to January 2016. The data collection was the application of a questionnaire to obtain socioeconomic-demographic, lifestyle, health condition and related to pregnancy information, blood collection and oral assessment, with full mouth examination which included the following parameters: probing depth, clinical attachment level and bleeding on probing. Participants were classified according to the level of periodontitis severity, mild, moderate and severe, using two defining criteria. They were also classified according to the presence or absence of ACD. Association measurements between exposure and outcome were estimated using Poisson regression analysis, obtaining the prevalence ratio (PR) and confidence intervals at 95% (95% CI). Results: the final sample included 616 pregnant women, of which 16.56% (102) were diagnosed with ACD. The presence of periodontitis ranged from 16.72% to 67.53%, according to the definition criterion. There was no association between levels of periodontitis severity and ACD nor between periodontitis and ACD for both studied criteria: PRcrude = 0.60, 95% CI: [0.33 to 1.08] and PRcrude = 0.89, 95% CI: [0.76 to 1.05], even after adjustment for the following confounders: schooling level, smoking habit, age, number of prenatal consultations, parity and toothache in the last six months, PRadjusted = 0.61, 95% CI: [0.34 to 1.09] and PRadjusted = 0.90 , 95% CI: [0.76 to 1.05]. Conclusions: the findings of this research indicated that the presence of periodontitis, regardless of the severity level is not associated with the ACD, although there is a high frequency of these diseases in the studied group. Additional studies are needed to confirm these results, considering the importance of the two diseases as public health problems, as well as the relevance of the pregnancy.